Independensi, Integritas, Serta Kompetensi Auditor Terhadap Kualitas Audit dengan Skeptisisme Profesional Sebagai Variabel Pemoderasi: Independence, Integrity and Auditor Competence Against Audit Quality with Professional Skepticism as a Moderating Variable. - Santoso, Rizky Darmawan; Budi Riharjo, Ikhsan; kurnia, kurnia (Universitas Muhammadiyah Sidoarjo, 2020)
Abstract The purpose of this study is to determine the effect of independence, integrity and competence on audit quality and find out if it is proven that professional skepticism is able to moderate the effect of independence, integrity, competence, respectively on audit quality. The data collection method used is by distributing questionnaires to all public accounting firms (KAP) in the city of Surabaya. The sample selection technique uses a purposive sampling technique with KAP auditors as research subjects. The results showed that the higher the independence, integrity and competence, the better the audit quality would be. The moderating variable professional skepticism is able to moderate the positive influence of independence on audit quality, and negatively moderate the effect of integrity on audit quality but is not able to moderate the effect of competence on audit quality. Keywords: independence, integrity, competence, professional skepticism, audit quality.